Chapter (When) Is Adblocking Wrong? - Douglas, Thomas (Oxford University Press, 2021)
In this chapter, I examine three deontological objections to adblocking: the objection from property (according to which adblocking involves accessing another's property without satisfying the conditions placed on such access by the owner), the objection from complicity (according to which, by blocking ads, consumers become complicit in wrongdoing of adblocking software providers), and the objection from freeriding (according to which adblocking consumers free-ride on other consumers who allow ads to be served). I argue that, though these objections plausibly establish the moral impermissibility of some instances of adblocking, they do not, even collectively, establish a blanket moral prohibition on adblocking, as it is currently done.